Antioxidation enhancement and siliconization mitigation for SiC coated C/C composites via a nano-structural SiC porous layer. (January 2022) - Li, Tao; Zhang, Yulei; Fu, Yanqin; Sun, Jia
Abstract: A reactive nano-structural SiC porous layer on C/C surface was pre-prepared via a slurry-dipping and reaction-sintering method, using Si, C and Al2 O3 powders as raw materials. Pre-introduction of nano-structural SiC porous layer helped to form a dense sintered SiC coating by the pack cementation (PC), which provided excellent oxidation protection for C/C substrate under different conditions at 1773 K and mitigated the siliconization reaction of free silicon during the PC process. Results showed that the modified SiC coating had a mass loss of only 0.03% after 50 thermal cycles between room temperature and 1773 K in air. And the mass loss reduced by 4.31 and 2.25 times after isothermal oxidation in dry air and wet oxygen atmosphere at 1773 K, respectively. Furthermore, because of the delaying effect of SiC porous layer on free silicon infiltrating into C/C substrate, the bending strength of modified SiC-coated C/C composites has increased by 93.0%. Highlights: A nano-structural SiC porous layer was fabricated via a facile route. Introducing nano-structural porous layer enhances the densification of SiC coating. The inhibiting effect of SiC layer on siliconization erosion improves the mechanical properties of coated samples.